Studi literatur problematika penguasaan nahwu pada mahasiswa pemula: dalam pembelajaran bahasa arab - Saraswati, Widya Kirana (Maliki Interdisciplinary Journal, 2026)
Mastering Arabic grammar is often considered challenging because Arabic sentences have a complex structure, which is a major obstacle for students who are just beginning to learn the language. This study aims to evaluate the problems faced by beginner students in understanding nahwu when learning Arabic and to formulate comprehensive recommendations for solutions. The method used in this study is a literature review, analyzing relevant literature, such as journal articles and books, to explore the causes of the existing problems. The results of this study show that new students often experience obstacles in mastering nahwu due to the complexity of the material (the gradual structure of nahwu and the use of technical terms), conventional teaching methods that focus more on memorization, and a lack of opportunities for communication practice in learning. As a result, their understanding of nahwu tends to be narrow and cannot be effectively applied in Arabic language skills. As a solution, this study recommends the application of a gradual teaching method that starts from basic concepts (i'rab signs, sentence types). A practical learning program that provides real sentence examples is also recommended, along with the use of interactive teaching methods (discussions, group work), and the integration of nahwu learning with everyday Arabic language activities. It is hoped that by implementing this approach, students' motivation and understanding of nahwu will increase and support the development of more solid Arabic language skills.